2009
DOI: 10.1348/014466508x336167
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain syndrome associated with health anxiety: A qualitative thematic comparison between pain patients with high and low health anxiety

Abstract: The phenomenological information both informs and supports the idea that the cognitive-behavioural model of health anxiety can be adapted for the understanding of and development of treatments for pain patients with health anxiety. The findings also challenge the common practice of 'lumping' pain patients into a single group and underline the importance of matching treatments to the patients' psychological characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 65 publications
4
33
0
Order By: Relevance
“…Broadly replicating the approach of a thematic comparison in a different patient group (Tang et al, (2009), the data were analyzed in three main stages:…”
Section: Discussionmentioning
confidence: 99%
“…Broadly replicating the approach of a thematic comparison in a different patient group (Tang et al, (2009), the data were analyzed in three main stages:…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, these general psychological factors have been identified as independent predictors of the severity of sleep complaints, over and above the effects of demographics and pain. A small number of specific cognitive-behavioural processes have also been linked to the degree of insomnia severity in chronic pain; these include pain attention (17), affective interpretation of pain (8), pre sleep pain related thoughts (13), dysfunctional beliefs and attitude about sleep (18) and the idea of using sleep as an escape from pain (9).…”
Section: Clinical and Psychological Correlatesmentioning
confidence: 99%
“…I can't take this anymore" [1] Chronic pain can be lethal; its unwelcome presence and debilitating impact can considerably increase the risk of suicidality among people living with chronic pain [2][3][4]. Several large-scale epidemiological surveys have now established that the presence of any pain condition doubles the risk of suicidal ideation (passive thoughts or active intent of committing suicide) and trebles that of suicide attempt in the general population [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Mental defeat encapsulates the deeper impact of chronic pain on a person's sense of self and identity. Thoughts and images of mental defeat reported by chronic pain patients are not dissimilar to those reported by victims of torture or assault who subsequently develop chronic depression and posttraumatic stress disorder (PTSD) [1]. In fact, in the depression and PTSD literature, mental defeat has been highlighted as a key cognitive predictor of symptom severity and treatment response [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%